Mental health and well-being of elite youth athletes: a scoping review - Gwyther, K.; Pilkington, V.; Bailey, A. P.; Mountjoy, M.; Bergeron, M. F.; Rice, S. M.; Purcell, R. (British Journal of Sports Medicine, 2024)
Background There is increasing recognition of the prevalence and risk factors for mental health symptoms and disorders among adult elite athletes, with less research involving elite youth athletes. This scoping review aimed to characterise the mental health and well-being of elite youth athletes who travel internationally and compete for their sport.